ANALISIS PENGARUH NON-TARIFF MEASURES (SANITARY AND PHYTOSANITARY) TERHADAP VOLUME EKSPOR IKAN TUNA KE NEGARA TUJUAN EKSPOR - Suwandari, Ni Ketut Riski Rahayu; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024, 2024)
This study aims to analyze the effect of Gross Domestic Product (GDP) per capita, economic distance, real exchange rate, and dummy SPS simultaneously and partially on volume of tuna exports to export destination countries. The analysis technique used in this study was panel data regression. The results of this study found that simultaneously GDP per capita, economic distance, real exchange rate, and dummy SPS affect the volume of tuna exports to export destination countries. GDP per capita and real exchange rate partially have a positive and significant effect, dummy SPS partially affects the volume of tuna exports to export destination countries. Meanwhile, economic distance has a negative and insignificant effect on the volume of tuna exports to export destination countries. The implication of this study is that the existence of GDP per capita and changes in the real exchange rate will increase the export volume of Indonesian tuna, the SPS action will reduce the export volume of Indonesian tuna, and the long economic distance will reduce the export volume of Indonesian tuna although not significantly.